2021
DOI: 10.5812/pedinfect.115548
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Severe Acute Respiratory Infections Due to Rhinovirus/Enterovirus Complex in Children and Their Comparison with Those of Respiratory Syncytial Virus

Abstract: Background: Acute respiratory tract infections (ARTIs) are one of the main causes of morbidity and mortality in children under the age of five worldwide. Objectives: The objective of this research was to describe the main characteristics of hospitalized patients with ARTI caused by the rhinovirus/enterovirus (RV/EV) complex and the risk factors associated with severe infection. Methods: This was a retrospective descriptive study in patients from one month to 18-years-old who had been hospitalized for ARTI betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Similarly, mNGS would have the potential to identify the presence of viral or bacterial co-infection. A recent study found (42). Using mNGS could guide against the coexistence of these coinfections, which in risk groups is associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, mNGS would have the potential to identify the presence of viral or bacterial co-infection. A recent study found (42). Using mNGS could guide against the coexistence of these coinfections, which in risk groups is associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mNGS would have the potential to identify the presence of viral or bacterial co-infection. A recent study found that viruses such as Rhino/Enterovirus have a high prevalence of coexisting with other viruses and patients–especially premature children with bronchopulmonary dysplasia and heart disease–with these simultaneous viruses are associated with worse clinical outcomes ( 42 ). Using mNGS could guide against the coexistence of these coinfections, which in risk groups is associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%